Writing wars: authorship and American war fiction, WWI to present - Eisler, David F. (University of Iowa Press, 2022)
"Who writes novels about war? For nearly a century after World War I, the answer was simple: soldiers who had been there. The assumption that a person must have experienced war in the flesh in order to write about it in fiction was taken for granted by writers, reviewers, critics, and even scholars. Contemporary American fiction tells a different story. Less than half of the authors of contemporary war novels are veterans. And that's hardly the only change. Today's war novelists focus on the psychological and moral challenges of soldiers coming home rather than the physical danger of combat overseas. They also imagine the consequences of the wars from non-American perspectives in a way that defies the genre's conventions. To understand why these changes have occurred, David Eisler argues that we must go back nearly fifty years, to the political decision to abolish the draft. The ramifications rippled into the field of cultural production, transforming the foundational characteristics- authorship, content, and form-of the American war fiction genre"--
Includes bibliographical references and index
Keywords: Geschichte 1918-2022; USA; Hochschulschrift